2018
DOI: 10.4049/jimmunol.1800139
|View full text |Cite|
|
Sign up to set email alerts
|

Bcl2L12 Contributes to Th2-Biased Inflammation in the Intestinal Mucosa by Regulating CD4+ T Cell Activities

Abstract: The Th2-biased inflammation and immune deregulation play a critical role in the pathogenesis of ulcerative colitis (UC). Recent studies indicate that the Bcl2-like protein 12 (Bcl2L12) is associated with immune deregulation of UC. This study aims to investigate the role of Bcl2L12 in the induction of aberrant Th2-biased inflammation. In this study, peripheral blood samples were collected from patients with inflammatory bowel disease. The Th2 cell activities were analyzed by flow cytometry, real-time quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 36 publications
(43 reference statements)
4
21
0
Order By: Relevance
“…It was lately found that Bcl2L12 was also involved in the development of other types of cancer with its anti‐apoptotic activities . Further reports indicate that Bcl2L12 is associated with the immune deregulation . The present study has added novel information to this study field that Bcl2L12 regulates CD4 + T cell activities by compromising the apoptosis machinery to induce defects of apoptosis in CD4 + T cells.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…It was lately found that Bcl2L12 was also involved in the development of other types of cancer with its anti‐apoptotic activities . Further reports indicate that Bcl2L12 is associated with the immune deregulation . The present study has added novel information to this study field that Bcl2L12 regulates CD4 + T cell activities by compromising the apoptosis machinery to induce defects of apoptosis in CD4 + T cells.…”
Section: Discussionmentioning
confidence: 62%
“…20 Further reports indicate that Bcl2L12 is associated with the immune deregulation. 12,13 The present study has added novel information to this study field that Bcl2L12 regulates CD4 + T cell activities by compromising the apoptosis machinery to induce defects of apoptosis in CD4 + T cells. On the other hand, the defects of apoptosis in CD4 + T cells may be also a result of Th2 polarization because IL-5 can increase the expression of Bcl2L12 in CD4 + T cells.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Our previous studies indicate that Bcl2L12 plays a critical role in the pathogenesis of Th2 polarization [17]. We wondered if the low serum sCD83 levels were also associated with the over expression of Bcl2L12 in sTh2 cells.…”
Section: Serum Levels Of Scd83 Negatively Correlate With Bcl2l12 Exprmentioning
confidence: 97%